Odpowiedzi

2010-02-04T19:29:28+01:00
A) -3xy³+3xy-(2xy³-xy) dla x=-1, y=2

-3xy³+3xy-2xy³+xy = -5xy³ + 4xy

-5*(-1)*2³ + 4*(-1)*2 = 5*8 -8 = 32

b) -(-48a²+10a)-(-4a-a²) dla a= - 1/7

48a²-10a+4a+a² = 49a² - 6a

49*(-1/7)² - 6*(-1/7) = 49 * (1/49) - (-6/7) = 1 + 6/7

c) -(12√c-c)+(-8c+13√c) dla c=4

-12√c+c-8c+13√c = √c - 7c

√4 - 7*4 = 2 - 28 = -26
50 4 50
2010-02-04T19:36:31+01:00
A) -3xy³+3xy-(2xy³-xy)= dla x=-1, y=2
-3xy³+3xy-2xy³+xy=
-5xy³+4xy=
-5*(-1)*2³+4*(-1)*2=
-5*(-1)*8+(-8)=
40-8=32

b) -(-48a²+10a)-(-4a-a²)= dla a= - 1/7
48a²-10a+4a+a²=
49a²-6a=
49*(-1/7)²-6*(-1/7)=
49*1/49-6/7=
1-6/7=1/7

c) -(12√c-c)+(-8c+13√c)= dla c=4
-12√c+c-8c+13√c=
-12√4+4-8*4+13√4=
-12*2+4-8*4+13*2=
-24+4-32+26=-26

13 3 13